2015
DOI: 10.4172/2090-5025.1000086
|View full text |Cite
|
Sign up to set email alerts
|

Does Sandblasting Improve Bond Strength between Nano-ceramic Resin and Two Different Luting Composites?

Abstract: Purpose: To assess the influence of a sandblasting surface treatment on the shear bond strength (SBS) between a recently introduced Resin Nano-Ceramic (RNC) CAD/CAM material and two resin cements.Methods: 40 RNC blocks were divided into two groups (n=20): a control (C) and a test group (S_50) to which air abrasion (50 µm, 0.28 MPa, and 10s) was applied. Each group was divided into two subgroups (n=10) according to the applied luting material: a self-etch dual-cure resin cement (LP) and a dual-cure resin cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…This might be due to the fact that mechanical sandblasting caused an increase in the irregularity and the surface free energy so increased the bond strength. (15) These results were in consistent with another study which showed that the abrasion process removed contaminated layers and created a rough surface for mechanical retention by the luting agent. Additionally, surface roughening increased the surface area for efficient bonding and could lead to physicochemical changes such as an increase in surface energy and wettability.…”
Section: Discussionsupporting
confidence: 91%
“…This might be due to the fact that mechanical sandblasting caused an increase in the irregularity and the surface free energy so increased the bond strength. (15) These results were in consistent with another study which showed that the abrasion process removed contaminated layers and created a rough surface for mechanical retention by the luting agent. Additionally, surface roughening increased the surface area for efficient bonding and could lead to physicochemical changes such as an increase in surface energy and wettability.…”
Section: Discussionsupporting
confidence: 91%